The Effect Of Juice Mangosteen Rind (Garcinia Mangostana L.) To Blood Sugar Levels And Histological Of Pancreatic Rats With The Induction Of Streptozotocin - Maris Kurniawati; Chanif Mahdi; Aulanni'am Aulanni'am (The Journal of Pure and Applied Chemistry Research, 2014)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by high blood sugar levels as a result of insufficiency of insulin function. Xanton a bioactive compound in the mangosteen rind is convinced to possess antidiabetic effects. There for, in this study effect of juice mangosteen rind (Garcinia mangostana L.) on blood sugar levels, and histological features of pancreatic rats with the induction of streptozotocin was investigated. This research using experimental rats species of Rattus norvegicus Wistar strain male. Rats were divided into 3 groups, the first group was the control without any treatments, group II was sick rat group, and group III was therapy rat group treated with juice mangosteen rind (a dose of 110 mg/kg body weight) by sonde for 2 consecutive weeks. Then,blood sugar levels of all rat groups were measured along with observation of their pancreatic histological. The results showed that the blood sugar level in therapy rat group (104.7 ± 10.9 mg/dL) is not significantly different with that of rat control group (108.5 ± 19.5 mg/dL), revealing effectiveness of therapy. Conservely, blood sugar level remained high in sick rat group (163.8 ± 16.2 mg/dL). Juice mangosteen rind can improve conditions of the pancreatic histology rat with the induction of streptozotocin.